A Comparison of Photoprotective Mechanism in Different Light-Demanding Plants Under Dynamic Light Conditions - Shuang, Sheng-Pu; Zhang, Jin-Yan; Cun, Zhu; Wu, Hong-Min; Hong, Jie; Chen, Jun-Wen (Frontiers in Plant Science, 2022)
Light intensity is highly heterogeneous in nature, and plants have evolved a series of strategies to acclimate to dynamic light due to its immobile lifestyles. However, it is still unknown about whether there are differences in photoprotective mechanisms among different light-demanding plants in response to dynamic light, and thus the role of non-photochemical quenching, electron transport and light energy allocation of photosystem in photoprotection needs to be further understood in different light-demanding plants. The activities of PSII and PSI in shade-tolerant species Panax notoginseng, intermediate species Polygonatum kingianum and sun-demanding species Erigeron breviscapus were comparatively measured to elucidate photoprotection mechanisms in different light-demanding plants under dynamic light. The results showed that non-photochemical quenching (NPQ) and PSII maximum efficiency (Fv'/Fm') of E. breviscapus were higher than the other two species under dynamic high light. Meanwhile, cyclic electron flow (CEF) of sun plant is larger under transient high light condition since the slope of post-illumination, P700 dark reduction rate and PQ pool were greater. NPQ was more active and CEF was initiated more readily in shade plants than the two other species under transient light. Moreover, sun plants processed higher quantum yield of PSII photochemistry (ΦPSII), quantum yield of photochemical energy conversion (Y(I)) and quantum yield of non-photochemical energy dissipation due to acceptor side limitation (Y(NA). While the constitutive thermal dissipation and fluorescence (Φf,d) and quantum yield of non-photochemical energy dissipation due to donor side limitation (Y(ND)) of PSI were higher in shade plants. These results suggest that sun plants had higher NPQ and CEF for photoprotection under transient high light, and mainly allocated light energy through ΦPSII and ΦNPQ. While shade plants had a higher Φf,d and a larger heat dissipation efficiency of PSI donor. Overall, it has been demonstrated that the photochemical efficiency and photoprotective capacity are greater in sun plants under transient dynamic light, while shade plants are more sensitive to transient dynamic light.